Genetic algorithm for flexible job shop scheduling problem - A case study - Guevara, Gabriela (2015)
This paper proposes the impact assessment of the workers in the optimal time of operations in a Flexible Job Shop Scheduling Problem. In this work, a real enterprise was studied. The problem consists in finding the workers operations schedule, taking into account the precedence constraints. The main objective is to minimize the finish time of the last task completed in the schedule. The genetic algorithm was used to solve the optimization problem and some numerical results are presented.